Enhancing Students’ Cognitive Skills through Interactive Learning Strategies in Science Education - Chantrea, Moeurn (Educative: Jurnal Ilmiah Pendidikan, 2025)
Toward the close of the 1990s, the Royal Government of Cambodia commenced the privatization of higher education institutions to increase options for 12th-grade graduates seeking to continue their studies. Consequently, the total number of higher education institutions in Cambodia has increased consistently, anticipated to hit 194 by 2025, along with a related rise in student enrollment. Studies reveal that the greatest student dropout rates happen in the initial year of education. Research within Cambodian higher education shows a limited scholarly focus on the first-year student experience, creating a critical gap in analyzing academic preparedness and transition efficacy needed to inform retention strategies. This article intends to explore the obstacles encountered by first-year students in higher education institutions in Cambodia. Utilizing document analysis along with the researchers' vast experience, knowledge, and expertise in student services, the study examines pertinent policy, institutional documents, reports, review literature, and research articles. The results indicate that first-year students face four main challenges: academic challenges, personal challenges, social challenges, and student services challenges. These findings underscore the innovative contribution of this research by demonstrating how enhancing student support services can directly improve learning outcomes, foster student retention, and drive continuous educational quality improvement within higher education institutions